Penguatan Kompetensi Finansial Melalui Program Pembelajaran Pengenalan Mata Uang Melalui Arisan Mengunakan Aplikasi Wheelofnamer - Bachtiar Abdul Ghani; Novan Ardy Wiyani (Syntax Idea)
This article describes why and how to strengthen financial competence in learning programs to recognize currency, therefore finance plays a crucial role to be applied to students. Introducing currency to students will be sufficient to influence understanding and knowledge regarding currency recognition through social gathering programs, as well as the wise use of money in the future. The role of the school is quite important in providing knowledge related to currency recognition learning for students. The cognitive nature of students who are still concrete and at the stage of development is quite effective in instilling the value of strengthening financial competence in the currency recognition learning program, with the aim that students who get their names out of the social gathering program on Mondays, which are rotated once a week should be able to manage their finances properly. good and know the types of currency, based on the needs and requirements as a student. The current state of students who tend to buy something without regard to financial principles can lead to irrationality in meeting needs. The research method used in this research is descriptive qualitative research method. From the results of this study, its usefulness boils down to developing learning designs that refer to the dimensions of knowledge and understanding, skills, and attitudes regarding financial financial competence so that they can create learning objectives and outcomes to increase students' understanding for their future.